Development of Android-Based Appy Pie Learning Media on Mathematics in Elementary School - Inas Sayyida Latifa; Aan Subhan Pamungkas; Trian Pamungkas Alamsyah; Indhira Asih Vivi Yandari (IKIP Mataram, 2020)
This research aimed to develop Android-based Appy Pie learning media in mathematics subjects, especially two-dimensional shape material. Moreover, to determine the validity level of the android-based Appy Pie learning media developed and to determine the students' responses after using android-based Appy Pie learning media. This research uses the 3D model (define, design, and development) as the modification result of the 4D model by Thiagarajan. The subjects of this research were 45 fourth-grade students of SDN Rawu. The result of this research is the average score of media experts validation is 91.11% which included in the “very feasible” category, the average score of material expert validation is 98.33% which included in the “very feasible” category. The average score of the students response is 91.11% that included in the “very good” category, so it can be concluded that the Android-based Appy Pie learning media is feasible to use in the two-dimensional shape material of fourth-grade.